Mechanisms of Enhancing the Role of Saudi Universities Management in Developing Economic Awareness among its Students in light of the prevailing Economic Climate – Field study on academic leaderships at King Abdulaziz, Tabuk and Taibah Universities) - Al-Hadrami, Nouf Khalaf (Journal of Educational and Psychological Sciences, 2020)
This study aimed to enhance the role of Saudi public universities departments in developing economic awareness of their students, in light of the prevailing economic climate at the present time. This study used the descriptive approach. The study sample was chosen using the simple random sample method with a number of (235). The questionnaire was the study tool for data collection.The study reached many results, most notably: The level of the role of the Saudi universities administration in developing economic awareness of its students came as a medium level. The results also highlighted the presence of a high degree of challenges that limit the level of the role of Saudi universities in developing economic awareness among their students. The study revealed that there are statistically significant differences between the averages of the study sample responses on the role of the Saudi universities administration in developing economic awareness of its students according to the university variable in favor of King Abdulaziz University. The study recommended several recommendations, the most prominent of which were: the necessity of applying the proposed mechanisms in Saudi universities.
Keywords: Saudi universities; economic awareness; economic climate; students